2011
DOI: 10.1111/j.1551-2916.2011.04547.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics of LaF3 Nanocrystals in an Oxyfluoride Glass

Abstract: Nanocrystallization of LaF 3 in a glass of composition 55SiO 2 -20Al 2 O 3 -15Na 2 O-10LaF 3 (mol%) has been achieved by heat treatment above the glass transition temperature. A maximum crystal size of 14 nm has been attained, with the crystalline fraction and crystal size dependent on the time and temperature of thermal treatment. The effect of lanthanum fluoride crystallization is noticeable from the microstructural and compositional changes in the glass matrix, which have been studied using several techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 40 publications
5
82
0
Order By: Relevance
“…Bocker et al [100] clearly showed that droplet phase separation is the initial step of the nano SrF 2 crystallization into silicate glass under thermal treatment. Hemono et al [159] and Pablos-Martin et al [167,25,265] studied the crystallization kinetics of LaF 3 nanocrystals in oxyfluoride SiO 2 -Al 2 O 3 -Na 2 O-LaF 3 glasses and came to the conclusion that phase separation in the glass body precedes crystallization and quenching of the melt produces homogeneous glass. Reheating of the aforementioned SiO 2 -Al 2 O 3 -Na 2 O-LaF 3 samples caused the appearance of the droplet-like glass surfases, the first one was enriched in LaF 3 , and the second phase contained more SiO 2 and Al 2 O 3 .…”
Section: Micro-liquationmentioning
confidence: 98%
“…Bocker et al [100] clearly showed that droplet phase separation is the initial step of the nano SrF 2 crystallization into silicate glass under thermal treatment. Hemono et al [159] and Pablos-Martin et al [167,25,265] studied the crystallization kinetics of LaF 3 nanocrystals in oxyfluoride SiO 2 -Al 2 O 3 -Na 2 O-LaF 3 glasses and came to the conclusion that phase separation in the glass body precedes crystallization and quenching of the melt produces homogeneous glass. Reheating of the aforementioned SiO 2 -Al 2 O 3 -Na 2 O-LaF 3 samples caused the appearance of the droplet-like glass surfases, the first one was enriched in LaF 3 , and the second phase contained more SiO 2 and Al 2 O 3 .…”
Section: Micro-liquationmentioning
confidence: 98%
“…Oxyfluoride glass ceramics not only possess the good mechanical strength and chemical durability of oxide glasses but also possess the low phonon energy of fluorides. Presently, most research on oxyfluoride glass ceramics is focused on oxyfluoride glass ceramics containing Pb x Cd 1 − x F 2 and LaF 3 nanocrystals [12][13][14][15]. However, the toxicity of PbF 2 and CdF 2 , and the high price of raw materials LaF 3 limit their application.…”
Section: Introductionmentioning
confidence: 96%
“…Rare earth ion doped oxyfluoride glass ceramics have received much attention because of their potential applications in fiber amplifiers, upconversion lasers, and three-dimensional displays [12][13][14][15][16][17][18][19][20][21][22]. In the glass ceramics, rare earth ions are selectively incorporated into the fluoride nanocrystals embedded among the oxide glassy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Na + initially charge compensates [AlO 4 ] − in the oxide phase. [24,25,43,47,[49][50][51] In these referred experiment studies, the time of the thermal treat-ment does not affect the crystal size. Owing to a more compact structure is formed in aluminosilicate oxide phase after fluoride phase separation, Na + is not preferred to bond to [SiO 4 ] and create NBOs in the aluminosilicate oxide-rich phase.…”
Section: [Mo X F Y ] With [Sio 4 ] and [Alo X F Y ] Consisting Of Thementioning
confidence: 99%
“…[19,20] Our previous results suggested that www.advancedsciencenews.com www.advtheorysimul.com the fluoride phase separation is a result of the immiscibility nature between the oxide and fluoride network. [21,22] Furthermore, fluoride crystals precipitate from the separated fluoride phase region under certain conditions, [23][24][25][26] meaning that the fluoride crystals have similar composition with the fluoride phase. Therefore, understanding the fluoride phase separation in oxyfluoride glass can not only help to explore the structure-property relationship between the amorphous glass structure and luminescence centers but can also help to predict the possible crystals to be precipitated and to design glass-ceramics with better luminescent properties.…”
Section: Introductionmentioning
confidence: 99%